PEMANFAATAN BPC-1 SEBAGAI BAHAN BAKU PATUNG GANESHA MERAH DAN PENGARUHNYA TERHADAP HARGA JUAL DAN PROFITABILITAS - Wiryawan, Suputra; Nyoman, Normal (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT The aims of this research that relate the using of castle massa BPC-1 as raw material of red ganesha statue prothotype (l 14 cm – w 9 cm – h 17 cm)  are: (1) To calculate cost of good manufactured red ganesha statue prothotype by activity-based costing method; (2) To determine cost price red ganesha statue prothotype by cost-plus pricing method; and (3) To recognize profititability red ganesha statue prothotype by gross profit margin, operating profit margin, and net profit margin method. The research results shew that: (1) The cost of good manufactured red ganesha statue prothotype (l 14 cm – w 9 cm – h 17 cm) was Rp 74.531,63 each unit, that followed by: Unit-Level Activity Cost Rp 65.940,69, Batch-Related Activity Cost Rp 3.578,66, Product-Sustaining Activity Cost Rp 4.006,53, dan Facility-Sustaining Activity Cost Rp 1.005,75; (2) The cost price red ganesha statue prothotype (l 14 cm – w 9 cm – h 17 cm) was Rp 96.891,12 each unit, that followed by: cost of good manufactured Rp 74.531,63, profit margin Rp 11.179,75, operating expense Rp 11.179,75 (marketing expense Rp 7.453,17 and general & administrative expense Rp 3.726,58). The actual cost price of red ganesha statue prothotype was undervalue about Rp 7.691,12 each unit than theoretical cost price; and (3) The Profit margin red ganesha statue prothotype (l 14 cm – w 9 cm – h 17 cm) was Rp 9.167.391,20 for gross profit margin, Rp 4.583.696,00 for operating profit margin, and Rp 4.258.116,30 for net profit margin.